2014
DOI: 10.1007/s10067-014-2692-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact and therapy of osteoarthritis: the Arthritis Care OA Nation 2012 survey

Abstract: Osteoarthritis (OA) is the fastest growing cause of disability worldwide. The aim of this study was to understand the impact of OA on individuals and to explore current treatment strategies. An online UK-wide survey of people with self-reported OA was conducted composed of 52 questions exploring the impact of OA, diagnosis and treatment, the role of health professionals and self-management. 4,043 people were invited with 2,001 respondents (49% response, 56% women, mean age 65 years). 52% reported that OA had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
78
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 31 publications
(35 reference statements)
7
78
0
Order By: Relevance
“…Approximately one-half of the participants reported current use of NSAIDs compared to approximately 25% for any non-opioid analgesic and even less for opioids, which is consistent with OA treatment guidelines (4) and similar to other studies of OA oral analgesics in UK (14) and the US (10). …”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Approximately one-half of the participants reported current use of NSAIDs compared to approximately 25% for any non-opioid analgesic and even less for opioids, which is consistent with OA treatment guidelines (4) and similar to other studies of OA oral analgesics in UK (14) and the US (10). …”
Section: Discussionsupporting
confidence: 81%
“…knee injection, topical creams, PT) was less common in our study. Approximately 50% of participants had ever had a knee injection, which is similar to U.S. Medicare data (35); in contrast, 16.9% (15) and 27.5% (14) of patients received knee injections in two studies from the UK, suggesting that joint injections may be more commonly used in the US. Thirty-two to fifty-seven percent of our participants reported current use of topical creams, which is consistent with Conaghan et al, who reported 46.5% and 4.3% of individuals with OA had used an anti-inflammatory gel and capsaicin gel, respectively (14), and with Porcheret et al, who reported 38.8% for topical NSAIDs (15), both among UK populations.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…[18] These treatments can be classified into three main categories: non-pharmacological, pharmacological, and surgical. Non-pharmacological treatments include reduction of weight on the affected joint or braces that mechanically stabilize the joint.…”
Section: Introductionmentioning
confidence: 99%
“…OA, also called degenerative joint disease, is a disease of the whole joint in which all articular structures are affected [2]. It is a chronic articular disease that affects millions of people in the world that is characterized by a loss of articular cartilage leading to narrowing of the joint space, increased joint friction, persistent pain, and functional impairment [3]. Until now, pharmacologic and nonpharmacologic modalities were commonly used to manage OA [4].…”
Section: Introductionmentioning
confidence: 99%